2006
DOI: 10.1186/1471-2334-6-130
|View full text |Cite
|
Sign up to set email alerts
|

How long do nosocomial pathogens persist on inanimate surfaces? A systematic review

Abstract: Background: Inanimate surfaces have often been described as the source for outbreaks of nosocomial infections. The aim of this review is to summarize data on the persistence of different nosocomial pathogens on inanimate surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

38
1,641
8
95

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 2,101 publications
(1,782 citation statements)
references
References 110 publications
38
1,641
8
95
Order By: Relevance
“…More effective antibacterial films are needed at present due to the increasing resistance of pathogenic bacteria to synthetic antibiotics when administered for long times [2]. Recently, Mills et al [3], Parkin et al [4][5][6][7], Foster et al [8], Dunlop et al [9] and Yates et al [10] have reported antibacterial films of Ag and Cu films on glass and thin polymer films by chemical vapor deposition (CVD) and in some cases sputtering techniques.…”
Section: Introductionmentioning
confidence: 99%
“…More effective antibacterial films are needed at present due to the increasing resistance of pathogenic bacteria to synthetic antibiotics when administered for long times [2]. Recently, Mills et al [3], Parkin et al [4][5][6][7], Foster et al [8], Dunlop et al [9] and Yates et al [10] have reported antibacterial films of Ag and Cu films on glass and thin polymer films by chemical vapor deposition (CVD) and in some cases sputtering techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The field of antibacterial Cu films/surfaces has gained much attention during the last decade since they decrease/eliminate hospital-acquired infections involving antibiotic-resistant bacteria surviving for long times (Foster et al 2010) (Dunlop et al 2010). The Cu films avoid chemicals to clean/disinfect hospital rooms leaving residues after use (Kramer et al 2006). Recently, Gabbay et al (2006), Borkow and Gabbay (2008) and also Gedanken (2004) have reported the application of Cu textiles composites as antimicrobial surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Survival on dry inanimate surfaces can be between 3 days and 4 months, depending on the strain, and contributes to the successful persistence of Acinetobacter infections in health care settings [5,6]. A. baumannii has been isolated from hospital equipment, bedding, furniture and staff [7].…”
Section: Introductionmentioning
confidence: 99%